Quantitative real time polymerase chain reaction (qRT‐PCR) and RNAscope in situ hybridization (RNA‐ISH) as effective tools to diagnose feline herpesvirus‐1‐associated dermatitis. Issue 6 (5th September 2019) - Mazzei, Maurizio; Vascellari, Marta; Zanardello, Claudia; Melchiotti, Erica; Vannini, Susanna; Forzan, Mario; Marchetti, Veronica; Albanese, Francesco; Abramo, Francesca
Abstract : Background: Felid herpesvirus type 1 (FHV‐1)‐associated dermatitis is characterized by facial and nasal involvement; clinical and histopathological manifestations may overlap with other dermatitides. Objective: To evaluate the realibility of qRT‐PCR‐2 − ΔΔC q and RNAscope in situ hybridization (RNA‐ISH) methods to diagnose FHV‐1‐associated dermatitis, in formalin‐fixed paraffin‐embedded (FFPE) tissues. Animals: Sixteen FFPE samples from cats with facial dermatitis and four controls were studied. Methods and materials: Based on histopathological features, cases were separated into: Group 1, samples with herpetic dermatitis (four); Group 2, samples with nonherpetic facial dermatitis (six); Group 3, samples with facial dermatitis of ambiguous nature (allergic or viral) (six); and Group 4, samples from healthy cats (four). A relative quantification using the 2 − ΔΔC q method was used to estimate the "upregulation" of each FHV‐1 target viral gene copies (glycoprotein‐B and thymidine‐kinase) relative to reference gene. Detection of FHV‐1 mRNA was performed using the RNAscope 2.5 detection kit. Results: By 2 − ΔΔC q analysis, upregulation of both FHV‐1 genes was observed in all samples from Group 1 and two of six from Group 3. No upregulation was identified in samples from groups 2 and 4. Positive mRNA hybridization signal was observed in all cases from Group 1 and two cases of Group 3. No positivity was observed in samples from groups 2 and 4. Conclusions and clinical importance: QRT‐PCR 2 −ΔΔCq analysis and RNA‐ISH can identify the FHV‐1 genome as causative agent of the associated dermatitis, even where inclusion bodies are not detectable. Both techniques are functional in retrospective studies, have greater specificity than conventional PCR, and may be proposed for research and diagnostic purposes. Abstract : Background Felid herpesvirus type 1 (FHV‐1)‐associated dermatitis is characterized by facial and nasal involvement; clinical and histopathological manifestations may overlap with other dermatitides. Objective To evaluate the realibility of qRT‐PCR‐2 −ΔΔCq and RNAscope in situ hybridization (RNA‐ISH) methods to diagnose FHV‐1‐associated dermatitis, in formalin‐fixed paraffin‐embedded (FFPE) tissues. Conclusions and clinical importance qRT‐PCR 2 −ΔΔCq analysis and RNA‐ISH can identify FHV‐1 genome as causative agent of the associated dermatitis, even where the inclusion bodies are not detectable. Both techniques are functional in retrospective studies, have greater specificity than conventional PCR and may be proposed for research and diagnostic purposes. Résumé: Contexte: La dermatite liée à herpesvirus félin de type 1 (FHV‐1) est caractérisée par des lésions faciles et nasales ; les manifestations cliniques et histopathologiques peuvent se superposer à d'autres dermatoses. Objectif: Evaluer la capacité des méthodes qRT‐PCR‐2 ‐ΔΔCq et hybridation in situ (RNA‐ISH) RNAscope pour diagnostiquer la dermatite associée au FHV‐1, dans les tissus fixés dans le formol et montés dans la paraffine (FFPE). Sujets: Seize échantillons de FFPE de chats avec dermatite faciale et quatre contrôles ont été étudiés. Matériels et méthodes: A partir des données histopathologiques, les cas ont été séparés en deux groupes : Groupe 1, échantillons avec dermatite herpétique (quatre) ; Groupe 2, échantillons avec dermatite faciale non herpétique (six) ; Groupe 3, échantillons avec dermatite faciale de nature ambiguë (allergique ou virale) (six) ; et Groupe 4, échantillons de chats sains (quatre). Une quantification relative à l'aide de la méthode 2 ‐ΔΔCq a été utilisée pour déterminer l'augmentation de chaque copie de gène viral cible de FHV‐1 (glycoprotéine‐B et thymidine‐kinase) relié au gène de référence. La détection d'ARNm de FHV‐1 a été réalisée à l'aide du kit de détection RNAscope 2.5. Résultats: Par analyse 2 ‐ΔΔCq, l'augmentation des gènes FHV‐1 a été observée pour tous les échantillons du Groupe 1 et deux des six du Groupe 3. Aucune augmentation n'a été identifiée dans les échantillons des groupes 2 et 4. Un signal d'hybridation mRNA positif a été observé dans tous les cas de Groupe 1 et deux cas du Groupe 3. Aucune positivité n'a été observée dans les échantillons des groupes 2 et 4. Conclusions et importance clinique: Les analyses QRT‐PCR 2 ‐ΔΔCq et RNA‐ISH peuvent identifier le génome de FHV‐1 comme agent causal de dermatite, même si des corps d'inclusion ne sont pas détectables. Les deux techniques sont possibles pour les études rétrospectives, ont une meilleure spécificité que la PCR conventionnelle et peuvent être proposées à des fins de diagnostic ou de recherche. Resumen: Introducción: la dermatitis asociada al herpesvirus tipo 1 (FHV‐1) se caracteriza por afectación facial y nasal; Las manifestaciones clínicas e histopatológicas pueden superponerse con otras dermatitis. Objetivo: evaluar la viabilidad de los métodos de hibridación in situ qRT‐PCR‐2 ‐ΔΔCq y RNAscope (RNA‐ISH) para diagnosticar la dermatitis asociada a FHV‐1, en tejidos embebidos en parafina fijados con formalina (FFPE). Animales: se estudiaron 16 muestras de FFPE de gatos con dermatitis facial y cuatro controles. Métodos y materiales: según las características histopatológicas, los casos se separaron en: grupo 1, muestras con dermatitis herpética (cuatro); grupo 2, muestras con dermatitis facial no herpética (seis); grupo 3, muestras con dermatitis facial de naturaleza ambigua (alérgica o viral) (seis); y grupo 4, muestras de gatos sanos (cuatro). Se usó una cuantificación relativa usando el método 2 ‐ΔΔCq para estimar la "regulación positiva" de cada copia del gen viral objetivo FHV‐1 (glucoproteína‐B y timidina‐quinasa) en relación con el gen de referencia. La detección del RNAm de FHV‐1 se realizó utilizando el kit de detección RNAscope 2.5. Resultados: mediante el análisis 2 ‐ΔΔCq, se observó una regulación positiva de ambos genes FHV‐1 en todas las muestras del Grupo 1 y dos de seis del Grupo 3. No se identificó una regulación positiva en las muestras de los grupos 2 y 4. Se observó una señal de hibridación de RNAm positiva en todos los casos del Grupo 1 y dos casos del Grupo 3. No se observó positividad en las muestras de los grupos 2 y 4. Conclusiones e importancia clínica: el análisis qRT‐PCR‐2 ‐ΔΔCq y RNA‐ISH pueden identificar el genoma de FHV‐1 como agente causante de la dermatitis asociada, incluso cuando los cuerpos de inclusión no son detectables. Ambas técnicas son funcionales en estudios retrospectivos, tienen mayor especificidad que la PCR convencional y pueden proponerse para fines de investigación y diagnóstico. Zusammenfassung: Hintergrund: Die feline Herpesvirus Typ 1 (FHV‐1) assoziierte Dermatitis wird charakterisiert durch Veränderungen im Gesicht und an der Nase; klinische und histopathologische Manifestationen könnten mit anderen Dermatitiden überlappen. Ziel: Eine Evaluierung der Verlässlichkeit von qRT‐PCR‐2 ‐ΔΔCq und Methoden der RNAscope in situ Hybridisierung (RNA‐ISH), um eine FHV‐1‐assoziierte Dermatitis aus Formalin‐fixiertem in Paraffin‐eingebettetem (FFPE) Gewebe zu diagnostizieren. Tiere: Sechzehn FFPE Proben von Katzen mit einer Dermatitis des Gesichts und vier Kontrollen wurden untersucht. Methoden und Materialien: Die Fälle wurden anhand der histopathologischen Merkmale folgendermaßen in Gruppen unterteilt: Gruppe 1, Proben mit Herpesdermatitis (vier); Gruppe 2, Proben mit Nicht‐Herpes‐bedingter Dermatitis des Gesichts (sechs); Gruppe 3, Proben von Gesichtsdermatitis unterschiedlicher Natur (allergisch oder viral)(sechs); und Gruppe 4, Proben von gesunden Katzen (vier). Eine relative Quantifizierung mittels 2 ‐ΔΔCq Methode wurde verwendet, um die „Upregulierung" eines jeden FHV‐1 Targets viraler Genkopien (Glykoprotein‐B und Thymidin‐Kinase) im Vergleich zum Referenzgen zu schätzen. Der Nachweis von FHV‐1 mRNA wurde mittels RNAscope 2, 5 Detection Kit durchgeführt. Ergebnisse: Mittels 2 ‐ΔΔCq Analyse wurde eine Upregulierung von beiden FHV‐1 Genen in allen Proben von Gruppe 1 und bei zwei von sechs der Gruppe 3 beobachtet. Eine nicht stattgefundene Upregulierung wurde bei den Proben aus den Gruppen 2 und 4 beobachtet. Ein positives mRNA Hybridisierungssignal wurde in allen Fällen von Gruppe 1 und bei zwei Fällen aus Gruppe 3 beobachtet. Es wurden keine positiven Ergebnisse in den Proben aus den Gruppen 2 und 4 beobachtet. Schlussfolgerungen und klinische Bedeutung: Die QRT‐PCR 2 ‐ΔΔCq Analyse und die RNA‐ISH können das FHV‐1 Genom als ursächlich für die damit einhergehende Dermatitis identifizieren, auch wenn keine Einschlußkörperchen gefunden werden können. Beide Techniken funktionieren auch in retrospektiven Studien, haben eine größere Spezifität als der konventionelle PCR und können für Forschung und diagnostische Zwecke empfohlen werden. 要約: 背景: ネコヘルペスウイルス1型(FHV‐1)関連皮膚炎は、顔面および鼻病変が特徴的である。臨床症状および組織病理学的兆候は、他の皮膚炎と重複する可能性がある。 目的: 本研究の目的は、ホルマリン固定パラフィン包埋(FFPE)組織においてFHV‐1関連皮膚炎を診断するqRT‐PCR‐2 ‐ΔΔCq 法およびRNAscope in situ hybridization (RNA‐ISH)法の信頼度を評価することである。 被験動物: 顔面皮膚炎の猫および4頭の対照猫から16FFPEサンプルを研究した。 材料と方法: 被験症例を病理組織学的特徴に基づいて分類した。グループ1、ヘルペス性皮膚炎サンプル(4)。グループ2、非ヘルペス性顔面皮膚炎サンプル(6);グループ3、不明瞭な性質(アレルギー性またはウイルス性)を持つ顔面皮膚炎サンプル(6);グループ4、健常猫サンプル(4)。 2‐DDCq法を用いた相対定量化を、参照遺伝子と比較した各FHV‐1標的ウイルス遺伝子コピー(糖タンパク質Bおよびチミジンキナーゼ)の「アップレギュレーション」を推定するために使用した。 FHV‐1 mRNAの検出は、RNAscope 2.5検出キットを用いて実行した。 結果: 2‐DDCq解析により、グループ1全サンプルおよびグループ3の2/6において両FHV‐1遺伝子のアップレギュレーションを観察した。グループ2および4サンプルではアップレギュレーションは確認されなかった。グループ1全症例およびグループ3の2症例が正のmRNAハイブリダイゼーションシグナルを観察した。。グループ2および4サンプルでは正のmRNAハイブリダイゼーションシグナルは観察されなかった。 結論と臨床的重要性: QRT‐PCR 2 ‐ΔΔCq 解析およびRNA‐ISHは、封入体が検出できない場合でも、関連皮膚炎の原因物質としてFHV‐1ゲノムを特定することができる。両手法は、回顧的研究において機能的であり、従来のPCR法と比較して特異性が高く、研究および診断目的に提案される可能性がある。 摘要: 背景: 猫I型疱疹病毒(FHV‐1)相关皮炎的特征是面部和鼻部出现病变;临床和组织病理学表现可能与其他皮炎存在交叉。 目的: 在福尔马林固定、石蜡包埋(FFPE)组织中, 用qRT‐PCR‐2 ‐ΔΔCq 和RNAscope 原位杂交法诊断FHV‐1相关皮炎, 评估此法的可靠性。 动物: 研究16个猫面部皮炎和4个对照FFPE样本。 方法和材料: 根据组织病理学特征, 将病例分为:第一组, 疱疹性皮炎样品(4个);第二组, 非疱疹性皮炎(6个);第三组, 性质不明的面部皮炎样本(过敏或者病毒性)(6个);第四组, 健康猫样本(4个)。用 2 ‐ΔΔCq 方法进行相对定量, 评估每个FHV‐1的病毒靶基因复制(糖蛋白B和胸苷激酶)的"上调"与参考基因的相关性。用RNAScope2.5检测试剂盒检测FHV‐1mRNA。 结果: 通过 2 ‐ΔΔCq 分析, 第一组全部样本和第三组6个样本中的2个都发现了FHV‐1基因上调。第二组和第四组的样本没有发现上调。第一组全部病例中和第三组的2个病例都显示有mRNA杂交阳性。第二组和第四组的样本无阳性反应。 结论和临床意义: qRT‐PCR‐2 ‐ΔΔCq 分析和RNA原位杂交可以确定FHV‐1基因组是引起皮炎的原因, 即使无法检测到包涵体。两种方法在回顾性研究中都有效, 比传统PCR具有更高特异性, 可用于研究和诊断。 Resumo: Contexto: A dermatite associada a herpesvírus felino tipo 1 (HVF‐1) é caracterizada por acometimento facial e nasal; as manifestações clínicas e histopatológicas podem se confundir com outras dermatopatias. Objetivo: Avaliar a confiabilidade dos métodos qRT‐PCR‐2 ‐ΔΔCq e hibridização RNAscope in situ (RNA‐ISH) no diagnóstico de dermatites associadas a HVF‐1, em amostras de pele fixadas em formol e parafinadas. Animais: Foram estudadas dezesseis amostras de pele fixadas em formol e parafinadas de gatos com dermatite facial e quatro controles. Métodos e materiais: Baseado nas características histopatológicas, os casos foram divididos em: Grupo 1, amostras com dermatite herpética (quatro); Grupo 2, amostras com dermatites não herpéticas (seis); Grupo 3, amostras com dermatite facial de natureza ambígua (alérgica ou viral) (seis); e Grupo 4, amostras dos gatos saudáveis (quatro). Utilizou‐se uma quantificação relativa através do método 2 ‐ΔΔCq para estimar a ativação de cada cópia de gene viral alvo (glicoproteína‐B e timidina‐quinase) relacionado ao gene de referência. A detecção do mRNA do HVF‐1 foi realizada utilizando o kit RNAscope 2.5. Resultados: A partir da análise 2 ‐ΔΔCq, a ativação dos genes de HVF‐1 foi observada em todas as amostras do Grupo 1 e em duas de seis do Grupo 3. Não foi identificada ativação nas amostras dos Grupos 2 e 4. Sinal positivo de hibridização de mRNA foi observado em todos os casos do Grupo 1 e em dois casos do Grupo 3. Não se observou nenhuma positividade nas amostras dos Grupos 2 e 4. Conclusões e importância clínica: A análise por QRT‐PCR 2 ‐ΔΔCq e RNA‐ISH foi capaz de identificar o HVF‐1 como agente causador nas dermatitis associadas, mesmo quando os corpúsculos de inclusão não puderam ser detectados. Ambas as técnicas são funcionais em estudos retrospectivos, possuem melhor especificidade que a PCR convencional, e devem ser propostos tanto na pesquisa quanto como método diagnóstico.